Lower extremity flap coverage following trauma - Khundkar, R (Elsevier, 2019)
Lower extremity injuries requiring soft tissue coverage comprises a significant proportion of these injuries worldwide. Reconstruction of the soft tissues overlying fractures is essential for bone union and reduction of infection thus improving function and reducing the rate of limb amputation. A systematic exploration and excision of the wound should be jointly performed by senior surgeons from Orthopaedic and Plastic Surgery. The grading of the injury and subsequent reconstruction of bone and soft tissue should only be planned once a thorough excision of all necrotic tissue has been performed. It is this thorough debridement and early flap coverage that contributes to infection-free bony union. This article explores the options for soft tissue flap coverage for the different zones in the lower limb.